WE2.1: Can communities of practice help us accelerate and improve our gender research? - Bailey, Arwen (Bioversity International and the International Center for Tropical Agriculture, 2022)
There is often just one gender researcher per project or program team or CGIAR initiative so gender research can be a lonely and challenging business due to lack of collaborative and critical discussion with fellow researchers. Collaboration helps researchers to develop and enrich their theory and practice, and share their experiences, doubts, successes and puzzles /conundrums. Communities of Practice (CoP) are one way to cross organizational boundaries to create overarching learning and knowledge communities, providing spaces for collaborations and conversations throughout a project cycle. CoPs have been described as "A gathering of individuals motivated by the desire to cross organizational boundaries, to relate to one another, and to build a body of actionable knowledge through coordination and collaboration." (World Bank). But what does it take to make a CoP successful? Objective In this session, I will offer some tips from research and experience, so that participants can use CoPs better to achieve their own objectives in gender research. I will draw on examples mainly from the Alliance Gender Nexus Enabler (active since 2015) and the CGIAR Gender Transformative Methodologies (just launched). Who would benefit The session would benefit anyone who is curious about the power of Communities of Practice and thinking of setting one up to exchange experiences and ideas, address challenges, and improve their research-for-development practice Format Format will be a presentation of around 30 minutes, then up to an hour to answer your questions. The session will cover: • Basics of CoP theory • What research and experience show works to make CoPs successful • Examples from two Gender CoPs, one old one new